The shell model of electron structure of negative hydrogen ion - Ваврух, М.; Дзіковський, Д.; Стельмах, О.; Vavrukh, M.; Dzikovskyi, D.; Stelmakh, O. (Lviv Politechnic Publishing House, 2019)
У межах нерелятивістського наближення одержано компактний наближений розв’язок рівняння Шредингера для іона H− у вигляді розкладу за поліномами Лежандра і варіаційними функціями типу Шулля–Льовдіна. Точність розрахунку енергії іона відповідає результатам, одержаним за допомогою багатопараметричних функцій Гіллєраса і Пекеріса.

In the frame of non-relativistic approximation, a compact approximate solution of the Schr¨odinger equation for the ion of H− has been obtained in the form of product for Legendre polynomials and variational functions of the Schull–L¨owdin type. The accuracy of calculation of ion energy is of the same order that the results obtained using the multiparametric functions of Hylleraas and Pekeris.
Оболонкова модель електронної структури негативного іона водню
Keywords: негативний іон водню; базисний підхід; варіаційний підхід; енергія іонізації; negative hydrogen ion; reference system approach; variation method; energy of ionization; 523.9; 523.9-7; 523.9-47